OPTIMALISASI PRODUKTIVITAS ALAT GALI MUAT WHEEL LOADER 900 DAN 800 DALAM PENCAPAIAN PRODUKSI BATUBARA DI PT. BARA TABANG KUTAI KARTANEGARA – KALIMANTAN TIMUR - Saputra, Mude Reza; Tibri, Tengku; Fitrah, Azhari (LPPM ISTP, 2024)
Bara Tabang is a company operating in the mining sector which is located in Pondok Pumpkin Village, Tabang District, Kutai Kartanegara Regency, East Kalimantan Province. The mining system used by PT. Bara Tabang is an open mining system (Surface Mining). Coal loading activities on the stockchrome (Coalpad) are carried out using a combination of Komatsu 900 wheel loader and Komatsu 800 wheel loader. This research aims to optimize production so that production that is not achieved can be achieved in the following year. In carrying out this research, the method used was the time barrier reduction method. Where in this method the author collects data by carrying out direct activities in the field, or data obtained from companies and others deemed necessary. In this research, theory and field data are combined to obtain a problem solving approach. With improvements in avoidable obstacle times, work efficiency has increased for the previous 900 wheel loader from 72.26% to 83.13%, while for the previous 800 wheel loader it was 73.47% to 84.41%. In carrying out mining activities, the production target for loading 900 wheel loaders and 800 weheel loaders is 4,000,000 MT/month. Achieving productivity in October with the number of tools working 6 units of Wheel loader 800 resulted in production results of 1,704,121 M/T/month, 3 units of Wheel loader 900 obtained production results of 2,595,542 M/T/month. So for 9 wheel loader units working, the production output was 4,299,663 M/T/month. This was done by improving work time constraints thereby increasing the work efficiency of the equipment by 10%.. Meanwhile, the comparison is based on calculations using the Talpac application for 3 900 wheel loader units of 1,893,600 M/T/month and for 6 800 wheel loader units of 2,883,600 M/T/month. So for 9 wheel loader units working the production output is 4,777,200 M/T/month